Efektivitas Konseling Cognitive Behavior Therapy Dalam Meningkatkan Kontrol Diri Siswa - Cici Yulia (Consilium : Berkala Kajian Konseling dan Ilmu Keagamaan, 2021)
Self-control is one of the main potential of the students must be developed. Inability to control themselves students in school resulted in the emergence of uncontrolled behavior as, breaking the school rules, undiscipline in the learning process at school. Aspects of self-control that should be developed by the students is the behavior control, control the mind (cognitive control), and control the decision (decisional control). This study aims to determine: (1) a picture of the self-control of students before and after a given cognitive behavior therapy approach; (2) the effectiveness of cognitive behavior therapy approach to increase self-control. The experimental research design with one group pretest-posttest design aims to test whether cognitive behavior therapy counseling approach with the group format can enhance students' self-control to be high. One group was selected using a technique using non-random sampling with purposive sampling method chosen from the Kelas X Teknik Kendaraan Ringan (TKR) SMKN 1 Koto Baru Dharmasraya. group consisted of 10 students. cognitive behavior therapy group counseling held during five meetings. Data on self-control are collected through the pretest and posttest, then analyzed using the Wilcoxon Signed Ranks Test with SPSS version 20.00.